Moringa oleifera supplemented foods in South Africa : A multidisciplinary approach combining consumer studies with physico-chemical and nutritional analyses - (:unkn) unknown (My University, 2021)
Malnutrition is a major challenge in South Africa (SA), particularly in Eastern Cape and Limpopo provinces, which are predominantly black and historically disadvantaged. This thesis aims to assess the potential of Moringa oleifera (MO) as a source of nutritional improvement in the diets of mothers and their children in these provinces. Known for its nutritional benefits, MO is a plant native to India, now cultivated in SA but not widely used for human nutrition. A two-part approach was followed in this thesis. The first part aims to understand how MO is perceived by consumers and how it can be integrated into the South African food repertory. A study of the knowledge, beliefs and consumption habits of MO allowed us to contrast two cultures, India and Africa (Nigeria, Ghana and SA). Findings from the first part revealed a difference in consumer knowledge and uses, however, no difference was observed in terms of beliefs. This implies that a positive attitude towards MO is not enough to promote its consumption. This study also showed that MO is also less embedded in the eating habits of South Africans than in the habits of the other two African countries. Observation of the eating habits of South African student mothers and their children showed a shift between their level of knowledge and what they actually do. Although they are aware of the importance of nutritional intake, they prefer to give their children foods they like even if they are not healthy. These students perceive MO more as a medicine than a food, but are not opposed to adding it as a nutrient supplement in their basic diet as long as the foods offered are good, available and easy to prepare. The objective of the second part of this thesis is to study the nutritional intakes of MO and the development of a food supplemented with MO leaves. The nutritional characterization of the MO leaf powder showed a digestibility of 75.95%. Pretreatment of the MO powder with high pressure, ultrasound and
Keywords: African Research